Formal-informal economy linkages and unemployment in South Africa - Davies, Rob; Thurlow, James (International Food Policy Research Institute, 2009)
South Africa’s high involuntary unemployment and small informal sector are attributed to an underperforming formal sector and barriers to entry in the informal sector. This paper examines the economywide linkages between the formal and informal economies while accounting for different types of informal activities. A multiregion empirically calibrated general equilibrium model is developed capturing both product and labor markets. Three policy options are considered. First, results indicate that trade liberalization reduces national employment. At the same time, it increases formal employment, hurts informal producers, and favors informal traders, who benefit from lower import prices. Past liberalization may, therefore, partly explain South Africa’s small informal sector and its concentration among traders rather than producers. Second, wage subsidies on low-skilled formal workers increase national employment but hurt informal producers by heightening competition in domestic product markets. This suggests that it is insufficient to examine unemployment policies by focusing only on labor markets. Third, unconditional cash transfers stimulate demand for informally produced products, thereby raising informal employment without undermining formal producers. The transfer does, however, place a large fiscal burden on the state and is less effective at reducing national unemployment than a wage subsidy. Overall, these findings underline the importance of distinguishing between the formal and informal sector implications of socioeconomic policies.